Effects of ambient conditions on the risk of pressure injuries in bedridden patients—multi‐physics modelling of microclimate - Zeevi, Tal; Levy, Ayelet; Brauner, Neima; Gefen, Amit (International wound journal, 2018)
Scientific evidence regarding microclimate and its effects on the risk of pressure ulcers (PU) remains sparse. It is known that elevated skin temperatures and moisture may affect metabolic demand as well as the mechanical behaviour of the tissue. In this study, we incorporated these microclimate factors into a novel, 3‐dimensional multi‐physics coupled model of the human buttocks, which simultaneously determines the biothermal and biomechanical behaviours of the buttocks in supine lying on different support surfaces. We compared 3 simulated thermally controlled mattresses with 2 reference foam mattresses. A tissue damage score was numerically calculated in a relevant volume of the model, and the cooling effect of each 1°C decrease of tissue temperature was deduced. Damage scores of tissues were substantially lower for the non‐foam mattresses compared with the foams. The percentage tissue volume at risk within the volume of interest was found to grow exponentially as the average tissue temperature increased. The resultant average sacral skin temperature was concluded to be a good predictor for an increased risk of PU/injuries. Each 1°C increase contributes approximately 14 times as much to the risk with respect to an increase of 1 mmHg of pressure. These findings highlight the advantages of using thermally controlled support surfaces as well as the need to further assess the potential damage that may be caused by uncontrolled microclimate conditions on inadequate support surfaces in at‐risk patients.